Seepage Characteristics Study of Single Rough Fracture Based on Numerical Simulation - Shidong Wang; Qing Zhang; Li Zhao; Yi Jin; Jiazhong Qian (Applied Sciences, 2022)
Fracture seepage is an important aspect of groundwater research, but due to the closure of fractures and the randomness of wall surface roughness, it is a challenge to carry out relevant research. Numerical simulation serves as a good way to solve this problem. As such, the water flow in single fracture with different shapes and densities of roughness elements (various bulges/pits on fracture wall surfaces) on wall surface was simulated by Fluent software. The results show that, in wider rough fractures, the flow rate mainly depends on fracture aperture, while, in narrow and close rough fracture medium, the surface roughness of fracture wall is the main factor of head loss of seepage; there is a negative power exponential relation between the hydraulic gradient index and the average fracture aperture, i.e., with increase of rough fracture aperture, both the relative roughness of fracture and the influence of hydraulic gradient decrease; in symmetrical-uncoupled rough fractures, there is a super-cubic relation between the discharge per unit width and average aperture; the rough fracture permeability coefficient K is not a constant which is affected by the scale effect and the density of roughness elements. Results found provide further understanding of rough fracture seepage.